Enhanced photoelectrochemical cell performance of Co doped ZnO nanoparticles sensitized by affordable mixed dyes as sensitizer - Kumbhar, Deepak; Kumbhar, Sarita; Dhodamani, Anant; Delekar, Sagar; Harale, Namdev; Nalawade, Rekha; Nalawade, Avinash (Inorganic and Nano-Metal Chemistry, 2021)
In the present investigation, a simple sol-gel approach has been employed for the synthesis of hexagonal wurtzite ZnO nanoparticles (NPs). X-ray diffraction (XRD) rietveld study and Raman analysis reveal the mislaid of the mixed phases of ZnO NPs after doping. The scanning electron micrographs and transmission electron microscopy confirm the formation of hexagonal disk-shaped NPs. FTIR, PL, EDX, XPS validate optical and stoichiometric concentration of Co in ZnO lattice. UV-visible DRS study shows absorption edge with humps to the red region of the spectrum with increasing the absorption strength and shortening of band gap as the content of Co (II) increases. Finally, the prepared samples were coated on the surface of cleaned FTO substrate through a simple doctor blade technique and sensitized with prepared dye. The ZnO photoanode shows 0.036% of efficiency (eta%) while the photoanodes of Co doped samples expose the enhanced efficiencies of 0.29%, 0.389%, 0.089%.
Keywords: Co doped ZnO; mixed dyes as sensitizer; Photoelectrochemical cell; sol-gel